Design Of A Multiwavelength Optical Light Source Using Optical Frequency Comb Generator (OFCG) - Thum , Ann (2005)
The purpose of this thesis is to design a traveling wave gigahertz optical phase modulator based on the optical frequency comb generation (OFCG) method. The optical modulator consists of an electro-optic (EO) phase modulator, which is modulated by the traveling microwaves, and is housed in a Fabry-Perot optical cavity to enhance the modulation depth. It is capable of generating a comb of optical frequencies (wavelengths) centered around 1550 nm and can be used as a light source for dense wavelenght division multiplexing (DWDM) in fiber optic communication.